The Effect of Big Book Media on Young Learners’ English Vocabulary Mastery and Learning Engagement - Putri Maisarah; Tanzil Huda; Widya Oktarini (Universitas Islam Negeri Palopo, 2026)
Vocabulary mastery is fundamental to young learners’ English language development, yet vocabulary instruction at the primary level is often dominated by memorization and drilling activities that may limit students’ engagement and vocabulary retention. Big Book media, which combines visual support and shared reading activities, has the potential to enhance vocabulary learning and promote active classroom participation. However, limited studies have simultaneously examined the impact of Big Book media on both vocabulary mastery and learning engagement among young learners in Indonesian EFL primary classrooms. Therefore, this study integrates quantitative and qualitative approaches to provide a more comprehensive understanding of the effectiveness of Big Book media. This study aimed to investigate the effect of Big Book media on young learners’ English vocabulary mastery and to explore students’ learning engagement during vocabulary learning activities. A convergent mixed-methods design was employed involving 52 Grade 1 students from an Indonesian public primary school, comprising 25 students in the experimental group and 27 students in the control group. Quantitative data were collected through vocabulary pre-tests and post-tests, while qualitative data were obtained through classroom observations and interviews. The results showed that students taught using Big Book media demonstrated greater improvement in vocabulary mastery than those receiving conventional instruction. The Mann–Whitney U test revealed a statistically significant difference between the groups (U = 129.000, Z = −3.857, p < .001), with a large effect size (r = .53). Qualitative findings indicated high levels of attention, participation, enthusiasm, and positive responses toward the use of Big Book media. Students reported that the illustrations and shared reading activities helped them understand and remember vocabulary more effectively. The findings suggest that Big Book media effectively improves vocabulary mastery and learning engagement among young learners, while demonstrating the value of integrating quantitative and qualitative evidence in EFL vocabulary research.